Luther [videorecording (DVD)] - Fiennes, Joseph, 1970-; Molina, Alfred, 1953-; Firth, Jonathan; Cox, Claire, 1975- (MGM Home Entertainment, 2004)
Regional princes and the powerful Catholic Church wield a fast, firm and merciless grip over 16th-century Germany. But when Martin Luther issues a shocking challenge to their authority, the people declare him their new leader - and hero. Even when threatened with violent death, Luther refused to back down, sparking a bloody religious revolution that shakes the entire continent to its core.